Evaluation of ticks biting humans in thrace province, Turkey [Trakya i̇llerinde i̇nsanlari tutan kenelerin deǧerlendirilemesi] - (:unkn) unknown (My University, 2010)
This study examined 1478 tick samples taken from humans who applied to the hospitals with tick bites in the provinces of Tekirdag, Kirklareli and Edirne in Thrace region of Turkey between May and November, 2007. The samples were evaluated in terms of species, developmental stage, gender, season and locality. The ticks were identified as Hyalomma spp. (76.05%), Rhipicephalus spp. (11.71%), Ixodes spp. (10.55%), Haemaphysalis spp. (1.48%), Dermacentor spp. (0.07%), Ornithodoros spp. (0.07%), and Argas spp. (0.07%). Majority of the tick samples were Hyalomma aegyptium nymphs (68.54%). According to the hospital application dates, tick bite cases occurred in August at most (30.11%). Tick bites by Ixodes spp. were abundant in the Black Sea coasts of the region. Based on localities, majority of the cases were reported from the urbanized areas (61.30%).
Keywords: Human; Thrace; Tick; Turkey